Plasmid- and Chromosome-Encoded Redundant and Specific Functions Are Involved in Biosynthesis of the Siderophore Anguibactin in Vibrio anguillarum 775: a Case of Chance and Necessity? - Alice, Alejandro F. (American Society for Microbiology, 2005)
We report the identification of a novel chromosome cluster of genes in Vibrio anguillarum 775 that includes redundant functional homologues of the pJM1 plasmid-harbored genes angE and angC that are involved in anguibactin biosynthesis. We also identified in this cluster a chromosomal angA gene that is essential in anguibactin biosynthesis.